Mardhâtillâh as The Final Purpose of Islamic Education - Gunawan, Heri (Jurnal Penelitian Pendidikan Islam, 2022)
This research begins with the idea that the purpose of Islamic education must be in accordance with the purpose of human life. The purpose of life is a very valuable thing that needs to be fought for earnestly. The greatest goal in life is none other than achieving the pleasure of Allah almighty. This research uses a qualitative approach with analytical descriptive method. The results of this study are that in the Qur'an there are many verses that contain the word pleasure (ridhā) with various derivations. Of the many words of pleasure that are united with the word Allah, only three sentences are found and all of them show that the pleasure (ridhā) of Allah almighty is obtained through a real struggle. In addition to the word mardhatillah, it is also found in other forms such as the word radhiya Allah. The pedagogical implication is that in essence the process of Islamic education must be able to lead students to reach the pleasure of Allah (mardhātillāh), not merely educate humans from the intellectual side, only physically proficient, but must make real humans, who are aware of nature holiness, who returns to Allah in a state of purity.